PENGARUH KNOWLEDGE SHARING DAN SELF EFFICACY TERHADAP EMPLOYEE PERFORMANCE MELALUI EMPLOYEE ENGAGEMENT PADA KARYAWAN BANK MANDIRI CCO SURABAYA - Nikmah, Dina Ulfatun; Budiono (Jurnal Ilmu Manajemen, 2024)
This study aims to test and analyse the effect of knowledge sharing and self efficacy on employee performance through employee engagement in Bank XYZ. The sampling technique used saturated samples with a total of 35 respondents. This research is included in the type of quantitative research using SEM-PLS analysis techniques assisted by SmartPLS software version 4. The results obtained are, knowledge sharing has no effect on employee engagement. Self efficacy has a positive effect on employee engagement. Employee engagement has no effect on employee performance. Knowledge sharing has a positive effect on employee performance. Self efficacy has no effect on employee performance. In the results of indirect relationships, employee engagement does not mediate the relationship between knowledge sharing and employee performance, and does not mediate the relationship between self efficacy and employee performance.